ANÁLISE ESTRATÉGICA DE UMA MICROEMPRESA DO MERCADO DE CICLISMO URBANO: STRATEGIC ANAYLISIS OF A MICRO ENTERPRIVE IN THE URBAN CYCLING MARKET - Sander, Natália Eloísa; Severo, Ana Júlia Brum; Borges, Mirele Marques; Lerman, Laura Visintaner (Brazilian Journal of Production Engineering, 2020)
The research sought to investigate the process of creating a strategic planning for a company that manufactures and sells accessories for urban cyclists, based on the methodology proposed by Müller (2003) combined with external and internal environment analysis tools, with The objective is to identify the strengths and weaknesses of the business, proposing an action plan with goals aligned with the company's strategic objectives. We used the method of literature review, company environment visit and interview with the founder to understand the business. The results were significant because it was possible to identify the points in which it is necessary to invest and set realistic goals for business growth. With the results presented, it can be concluded that the company has great growth potential, and the strategy adopted will make the company grow without losing its identity.